Badanie satysfakcji pracowników w organizacji gospodarczej : podejście klasyfikacyjne - Dziechciarz, Marta (Employee Satisfaction Survey in the Business Organization : Classification Approach, 2005)
Paper shows the application of the cluster analysis framework for the employee classification in the organization. Over 38 percent of employees took part in the job related satisfaction survey, which was conducted in a branch of the multinational company. The surveyed firm employs almost 600 people. According to the procedure proposed by Calinski and Harabasz - the classification into seven clusters was chosen. The k-means method has been used for classification. In the first step, 40 variables ware used as a base for classification. In the second step, each employee was described by 15 variables corresponding with motivation issues in the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 293-301